Basic Mapping Techniques Training: GPS Data Analysis with Microsoft Excel - Andrew Stefano; Sri Endayani (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Basic mapping techniques training with a focus on GPS data analysis using Microsoft Excel is a community service activity that aims to improve participants' skills in processing spatial data effectively. This training was held at the Rahmatullah Lempake Islamic Boarding School, North Samarinda, with the main participants being intermediate level students. This program is designed to provide a basic understanding of coordinate data collection using Garmin 60CSX GPS devices and processing survey data using Microsoft Excel. The training methods include theory sessions, hands-on practice in the field, and data processing simulations. The material provided includes an introduction to GPS functions, coordinate point retrieval techniques, data transfer from GPS to a computer, and data processing using basic Excel features such as tables, filters, graphs, and simple statistical functions. The results of the training showed an increase in the participants' ability to understand the basic concepts of mapping, manage coordinate data, and visualize survey results in the form of simple graphs and maps. Evaluation was carried out through pre-test and post-test to measure the level of understanding of participants before and after the training. The results of the evaluation showed an increase in the average score of the participants by 85%. In addition, participants were able to generate GPS data analysis reports independently using Microsoft Excel. This training is expected to be a solid foundation for participants to develop skills in the field of spatial data mapping and analysis, which are relevant in various fields such as geography, environment, and regional planning.